2014
DOI: 10.1016/j.exer.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for detecting lysosomal alkalinization and impaired degradation in fresh and cultured RPE cells: Evidence for a role in retinal degenerations

Abstract: Lysosomes contribute to a multitude of cellular processes, and the pH of the lysosomal lumen plays a central mechanistic role in many of these functions. In addition to controlling the rate of enzymatic degradation for material delivered through autophagic or phagocytotic pathways, lysosomal pH regulates events such as lysosomal fusion with autophagosomes and the release of lysosomal calcium into the cytoplasm. Disruption of either the steady state lysosomal pH or of the regulated manipulations to lysosomal pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 69 publications
0
65
0
Order By: Relevance
“…7,11 The molecular mechanisms underpinning CQ/HCQ retinopathy have been widely studied but are not fully understood. 41,42 Studies have reported that CQ and HCQ can cause distinctive abnormalities in the perifoveal photoreceptor inner segment/outer segment junction. 42 CQ and HCQ have also been proposed to induce RPE degeneration through several pathways including elevation of lysosomal pH, 41 increasing RPE permeability, 43 and binding to melanin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,11 The molecular mechanisms underpinning CQ/HCQ retinopathy have been widely studied but are not fully understood. 41,42 Studies have reported that CQ and HCQ can cause distinctive abnormalities in the perifoveal photoreceptor inner segment/outer segment junction. 42 CQ and HCQ have also been proposed to induce RPE degeneration through several pathways including elevation of lysosomal pH, 41 increasing RPE permeability, 43 and binding to melanin.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Studies have reported that CQ and HCQ can cause distinctive abnormalities in the perifoveal photoreceptor inner segment/outer segment junction. 42 CQ and HCQ have also been proposed to induce RPE degeneration through several pathways including elevation of lysosomal pH, 41 increasing RPE permeability, 43 and binding to melanin. 44 Our recent study showed that OATP1A2 is expressed in human RPE cells and, more importantly, that it mediates the uptake of atROL, a critical step in the human visual retinoid cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of cytoplasmic cAMP following stimulation of the adenosine A 2A receptor likely underlies this restoration of acidic lysosomal pH. Together, this implies that conversion of released ATP into adenosine by ectoenzymes may influence the production of lipofuscin and lipid oxidation in RPE cells (Guha et al, 2014). Whether the balance between ATP and adenosine influences the progression of diseases like age-related macular degeneration remains to be seen.…”
Section: Recent Findings Regarding Purines In the Eyementioning
confidence: 99%
“…Lysosomal pH Measurement-Lysosomal pH values in cells grown to confluence in 96-well plates were measured using LysoSensor Yellow/Blue DND-160 (Life Technologies) following a published protocol (31). Briefly, cells were loaded with 7.5 M LysoSensor Yellow/Blue DND-160 for 3 min at 32°C in DMEM, followed by washing with 20 mM HEPES buffer containing 145 mM KCl, 10 mM dextrose, and 1 mM MgCl 2 .…”
Section: Cav1mentioning
confidence: 99%